Hubungan Antara Kontrol Diri dan Penalaran Moral Dengan Kecurangan Akademik Pada Siswa SMA - Siti Mahmuda; Cipto Hadi; Mukhlis Mukhlis (LPPI Yayasan Almahmudi bin Dahlan, 2024)
Academic dishonesty is a phenomenon that is often encountered in the world of education and is considered normal and ignored by many people. Acts of cheating are certainly not in line with the values ​​instilled in character education which is the ultimate goal of education, namely to produce positive individuals. Two of the factors that can influence academic dishonesty are self-control and the level of moral reasoning. This study aims to determine the relationship between self-control and moral reasoning at the pre-conventional, conventional, and post-conventional levels, with academic dishonesty in students at SMAN X, Tambang District. The subjects of this study were 271 students in grades X and XI. The sampling technique was probability sampling with cluster random sampling. The data collection method used a scale of academic dishonesty, self-control, and moral reasoning. Data were analyzed using multiple linear regression analysis. The results of the study showed that together there was no significant relationship between self-control and moral reasoning at the pre-conventional, conventional, and post-conventional levels with academic dishonesty in students at SMAN X, Tambang District. Furthermore, there was no negative relationship between self-control and academic dishonesty in students at SMAN X, Tambang District. There is no negative relationship between pre-conventional level moral reasoning and academic dishonesty in students at SMAN X, Tambang District. There is no negative relationship between conventional level moral reasoning and academic dishonesty in students at SMAN X, Tambang District. There is no negative relationship between post-conventional level moral reasoning and academic dishonesty in students at SMAN X, Tambang District. This research on self-control and level of moral reasoning has not been proven to have an effect on reducing students' academic dishonesty.